Determination of unit characteristics of concrete linear creep/Betono tiesinio valkšnumo vienetinių rodiklių nustatymas - Balevičius, Robertas; Dulinskas, Eugenijus (Journal of Civil Engineering and Management, 2000)
It is very important to take into account time-dependent non-elastic deformations and variation of concrete mechanical characteristics in analysis of concrete structures. In codes of many countries, such as ENV 1992-1-1 (Eurocode) [1], ACI 209–92 (USA), AS 3600–1988 (Australia), DIN 4227 (Germany) and others, variation of creep deformations and physical mechanical characteristics with time is specified. The Code acting in Lithuania SNiT (Russ. СНиП 2.03.01-84*) [2] does not describe these characteristics directly. Calculation of time-dependent processes in the code acting in Lithuania SNiT [2] is associated with specific creep characteristics (specific creep, coefficient of creep) and with regulation of creep deformations. Such integral characteristics as steel prestress losses due to concrete creep associated with these specific characteristics are determined by empirical formulas which are obtained by tests with verification of stress and strain state of individual members. There are many investigations for determination of concrete creep characteristics. In the investigation [3], different relationships for determining specific characteristics of „young” and „old” concrete are proposed to apply, in recommendations [4] characteristics are presented according to their authors only for design, relationships presented in monograph [5] describe very well the creep of „young” concrete, code [6] regulates only limit values of creep characteristics. Characteristics determined by Eurocode [1] depend on the main factors influencing creep deformations but their relationship with regulations of the code [2] used in Lithuania is not clear. Therefore in this investigation relationships of specific creep characteristics for various compression grades of normal weight concrete describing great area of long-term deformations and taking into account the main factors influencing concrete creep were proposed. The proposed relationships also comply with regulation area of the code [2]. Analysis of specific concrete creep deformations based on steel prestress loss due to concrete creep calculation method [2] is presented in Chapter 2. Relationships for pure concrete specific creep (20–21) and for creep coefficient (23) were obtained. Comparison of these expressions with specific creep calculated according to code EC-2 [1] and recommended in [4] methods is shown in Figs 1–2. In Chapter 3, mathematical description of pure specific concrete creep (21) and of pure creep coefficient (23) based on theory of elastic plastic body is presented. Comparison of specific concrete creep characteristics determined by (35) and (37) relationships with analogous characteristics applied in codes [1, 4] is shown in Figs 3–4. In Chapter 4–5, coefficients (40), (41) evaluating the influence of water-cement ratio and quantity of cement paste on concrete creep deformations are presented. Analysis of experimental results of investigations of specific creep characteristics shows that time-dependent deformation properties depend not only on factors by which concrete creep is specified in codes and discussed in Chapters 3–4, but also on quantity of cement paste and water-cement ratio. Conformity of specific creep values determined by relationships (35) proposed by us taking into account coefficients (40–41) with standard concrete [3] and experimental creep investigation results [18] are shown in Figs 4–5. Statistical analysis of experimental and theoretical concrete creep deformation values determined according to the method proposed by us and by the code [1] is presented in Table 2. Mean ratios κ = C eksp (t, t 0)/C(t, t 0), mean square deviations σκ and coefficient of variation δκ were calculated. It was determined that theoretical values of specific creep calculated by the proposed method comply better (coefficient of variation δκ=27.7%) with presented test results than code EC-2 [1] (coefficient of variation δκ=31.9%) (Table 2). Analysis of method of calculation of steel prestress loss due to concrete creep according to the acting code SNiT [2] was made and relationships for linear specific creep of concrete B15—B60 grade were proposed to satisfy the accuracy of practical calculations in the area of regulations of the code [2]. Specific creep relationships presented take into account the most important factors effecting creep deformations: concrete grade, times of loading and observation, scale and ambient humidity, quantity of cement and cement paste. These relationships of specific creep characteristics and the method of evaluation of variation of concrete characteristics can be applied for analysis of concrete structures under the action of long-term loads. Article in Lithuanian. First Published Online: 26 Jul 2012